(untitled) (Global Journal of Human-Social Science, 2012)
Indigenous knowledge IK on plant species of material culture construction traditional arts and handicrafts used by the indigenous people in and around the Awash National Park ANP Ethiopia was conducted ethnobotanically The study aimed to investigate various aspects of IK on plant species of material culture A total of 96 informants between the ages of 20 and 80 were selected using prior information Data were collected using semi-structured interview guided field walk discussions and field observation similarity was applied for data analysis A total of 156 plant species of material culture belonging to 115 genera and 70 families were collected Of these 79 species serve as sources of raw materials for various construction purposes while 77 for traditional art and handicrafts Out of these 8 species were reported by the Afar Nation 14 by the Oromo Nation and the rest by both Nations About 93 of the species were reported with their vernacular local names where 73 were reported by the Afar Nation and 87 by the Oromo Nation Planting of these important species around homesteads and farmlands raising tree seedlings at nursery for large scale plantation better animal husbandry practices and improved shortage of grazing lands to minimize overgrazing of thatched grasses sustainable utilization and conservation of the species and awareness raising of the local people are recommended